2007
DOI: 10.1071/fp07121
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of acidic and novel basic forms of actinidin, the highly abundant cysteine protease from kiwifruit

Abstract: Actinidin is a cysteine protease found in Actinidia Lindl. (kiwifruit) species that affects the nutraceutical properties, processing characteristics and allergenicity of the fruit. Given the increased consumption of kiwifruit worldwide and the release of new varieties from different Actinidia species, the expression of actinidin mRNA and protein in a range of kiwifruit tissues was examined. Ten different actinidin mRNAs were identified encoding mature proteins of similar molecular weight (~24 kDa), but with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 55 publications
4
72
1
5
Order By: Relevance
“…On the other hand, actinidin was almost absent from two A. chinensis cultivars, 'Kohi' and 'Hort16A', and A. eriantha. Although the lower actinidin level in 'Hort16A' has already been reported (Maddumage et al, 2013;Nieuwenhuizen et al, 2007), 'Kohi' was newly found to contain only a little actinidin in this study. In the CBB-stained gel, a protein with slightly lower molecular mass than actinidin was detected in 'Koshin', 'Kohi', and 'Hort16A' (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…On the other hand, actinidin was almost absent from two A. chinensis cultivars, 'Kohi' and 'Hort16A', and A. eriantha. Although the lower actinidin level in 'Hort16A' has already been reported (Maddumage et al, 2013;Nieuwenhuizen et al, 2007), 'Kohi' was newly found to contain only a little actinidin in this study. In the CBB-stained gel, a protein with slightly lower molecular mass than actinidin was detected in 'Koshin', 'Kohi', and 'Hort16A' (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…S1), this cultivar could be a valuable source for breeding. To address the molecular basis for the lower actinidin level in 'Kohi', we first analyzed the gene expression of the actinidin-coding genes, Act1a and Act2a, because they have been shown to be detected in the ripe fruits of A. deliciosa 'Hayward' and A. chinensis 'Hort16A' (Nieuwenhuizen et al, 2007). Genomic PCR first confirmed the presence of Act1a and Act2a in 'Kohi' as well as in 'Hayward' and 'Hort16A' (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations